2010
DOI: 10.1258/ebm.2010.009366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noble gases on oxygen and glucose deprived injury in human tubular kidney cells

Abstract: The noble gas xenon has been shown to be protective in preconditioning settings against renal ischemic injury. The aims of this study were to determine the protective effects of the other noble gases, helium, neon, argon, krypton and xenon, on human tubular kidney HK2 cells in vitro. Cultured human renal tubular cells (HK2) were exposed to noble gas preconditioning (75% noble gas; 20% O(2); 5% CO(2)) for three hours or mock preconditioning. Twenty-four hours after gas exposure, cell injury was provoked with ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 40 publications
0
71
0
1
Order By: Relevance
“…The OGD assay was performed as previously described [15,16]. OGD solution is a balanced glucose-free salt solution (pH 7.4) consisting of 116 mmol/l NaCl, 5.4 mmol/l KCl, 0.8 mmol/l MgSO 4 , 1 mmol/l NaH 2 PO4, 26 mmol/l NaHCO 3 and 1.8 mmol/l CaCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The OGD assay was performed as previously described [15,16]. OGD solution is a balanced glucose-free salt solution (pH 7.4) consisting of 116 mmol/l NaCl, 5.4 mmol/l KCl, 0.8 mmol/l MgSO 4 , 1 mmol/l NaH 2 PO4, 26 mmol/l NaHCO 3 and 1.8 mmol/l CaCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…According to a described protocol (Rizvi et al, 2010), the OGD injury was produced by incubating with a glucose-free balanced salt solution (116 mmol/L NaCl, 5.4 mmol/L KCl, 0.8 mmol/L MgSO 4 , 1.0 mmol/L NaH 2 PO 4 , 1.8 mmol/L CaCl 2 , 26.2 mmol/L NaHCO 3 , 0.025 mmol/L phenol red, and 20 mmol/L sucrose) and exposing to a hypoxic environment of 5% CO 2 and 95% N 2 in air tight gas chambers at 37 °C for 4 h. These basic experimental conditions had been confirmed in our previous work. After 4 h culture, H9c2 cells were used in the experiment.…”
Section: Ogd Model Building and Experimental Groupingmentioning
confidence: 99%
“…In a different in vitro study of cultured neurons however, Rivzi et. al reported that normobaric helium was detrimental to neuron survival after hypoxia (Rizvi et al, 2009), and human tubular kidney cells (Rizvi et al, 2010).…”
Section: Application Of Helium In Neurologymentioning
confidence: 99%